2016
DOI: 10.1016/j.athoracsur.2015.08.054
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Radial Artery as an Additional Arterial Conduit During In-Situ Bilateral Internal Mammary Artery Grafting: A Propensity Score-Matched Study

Abstract: The use of the RA as an additional arterial graft in patients undergoing coronary artery bypass graft surgery with in-situ BIMA does not prolong late survival when compared with BIMA patients who received additional SVG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 20 publications
0
40
0
Order By: Relevance
“…In fact the use of the RA per se does not increase operative mortality [14] and the RA patency has been demonstrated to be non-inferior to SV patency at early angiographic follow-up [15]. Mohammadi et al [7] recently reported comparable long term survival in 249 matched pairs of patients receiving BITA+RA versus BITA+SV (P=0.44). However, the main limitation of this study is that many of the RA grafts (41.4%) were placed to noncritical coronary targets (ie, stenosis 50% to 70%).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…In fact the use of the RA per se does not increase operative mortality [14] and the RA patency has been demonstrated to be non-inferior to SV patency at early angiographic follow-up [15]. Mohammadi et al [7] recently reported comparable long term survival in 249 matched pairs of patients receiving BITA+RA versus BITA+SV (P=0.44). However, the main limitation of this study is that many of the RA grafts (41.4%) were placed to noncritical coronary targets (ie, stenosis 50% to 70%).…”
Section: Discussionmentioning
confidence: 75%
“…The right internal thoracic artery (RITA) has been advocated to further improve long term revascularization outcomes [2]. Whether the use of the radial artery (RA) [3][4][5] as third arterial conduit in addition to bilateral internal thoracic artery (BITA) grafting is associated with better survival when compared to BITA plus saphenous vein (SV) remains to be determined with isolated small series reporting conflicting results [6,7].…”
mentioning
confidence: 99%
“…Studies were excluded for the following reasons: no comparison between TAR and non‐TAR strategy (n = 32), sample population derived from a previously published and included series (n = 1), and lack of propensity score matching (n = 1). Consequently, 18 articles were included in our study . Mean age and mean body mass index of the included populations were 65.6 years (±7.6) and 27.1 (±1.7).…”
Section: Resultsmentioning
confidence: 99%
“…27 Contrarily, another group reported that use of an RA graft vs. SVG graft did not improve late survival in any age group. 28 Elderly patients requiring coronary revascularization tend to have decreased renal function and systemic arterial sclerosis. We think that the use of a 3rd or 4th arterial graft in elderly patients should be carefully determined based on the types of comorbidities that may be present, the patient's daily activity level, and angiographic findings.…”
Section: Disclosuresmentioning
confidence: 99%